Opportunities and obstacles to professional development of nurses in the opinion of the participants of emergency medicine specialisation - Nowicki, Grzegorz; Chilimoniuk, Beata; Goniewicz, Mariusz; Górecki, Marek (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Professional development is a process which takes place over time and within overall human development. It pertains to all employees, including especially healthcare system personnel (physicians, nurses, midwifes, paramedics). As a result of the constant advancements in medical sciences nurses are under an obligation to obtain professional qualifications at a high level, to gain a range of skills and to upgrade the knowledge necessary for normal functioning in a modern healthcare system. The Aim of the study. The aim of this work was to present the motives which mean that nurses undertake various forms of postgraduate training, to expose obstacles which render impossible their access to rising professional qualifications, and to indicate the most popular forms of professional training. Material and methods. The research was conducted from January until May 2010 among nurses who participated in specialist training in emergency nursing implemented in four cities/towns: Lublin, Zamość, Chełm, and Rzeszów. It covered a group of 77 people. The method employed in the research was a diagnostic survey, while the research tool was a survey questionnaire prepared by the author. Results and conclusions. An analysis of the research conducted has proven that nurses are interested in raising their professional qualifications through participation in various forms of postgraduate training. The conclusion was drawn that the most common motive for nurses undertaking postgraduate training is the will to widen their knowledge; and the financial barrier was the main obstacle on the way towards raising their professional qualifications. Studies, and specialist and qualifying training, are for nurses the most desirable forms of professional training. Problemy Pielęgniarstwa 2012; 20 (4): 473–479